Evaluating the Impact of Emotion Regulation Training on Aggressiveness in Elementary School Children - Ervina Kurniaty Cang; Yuspendi Yuspendi; Evany Victoriana (HUMANITAS published by Universitas Ahmad Dahlan., 2026)
Excessive aggressiveness during middle childhood can interfere with social functioning. Emotion regulation skills are essential at this stage, and training these skills is considered a relevant strategy to reduce aggressive behavior.This study aims to examine the effect of an emotional regulation training intervention on students aged 10–12 years at Elementary School “X” Bandung. Aggressiveness was measured using the Aggression Questionnaire by Buss and Perry (1992), Emotional regulation training provided as the intervention, while the Emotion Regulation Questionnaire (ERQ) by Gross and John (2003) was used as a manipulation check. The study employed a quasi-experimental pretest-posttest control group design with correlated groups. Data were analyzed using the Wilcoxon test to assess within-group differences and the Mann–Whitney U test for between-group comparisons. The results showed a significant reduction in aggressiveness among students who received the intervention (p = 0.000; p < 0.05). Based on Cohen’s (1988) classification, the intervention demonstrated a strong effect size (r = 0.88). These findings indicate that emotion regulation training effectively decreases aggressive behavior in middle childhood. The study highlights the importance of incorporating emotion regulation programs into elementary education to foster emotional competence and reduce behavioral problems